On Translating Camfranglais and Other Camerounismes - Vakunta, Peter (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractPost-colonial creative writers constantly resort to creolization and indigenization as modes of linguistic and cultural appropriation. In other words, these writers tend to transpose the imprint of their cultural backgrounds onto their fictional works.This paper addresses the challenges posed by language mixing to the literary translator. Rather than interrogate the theories of translation, the paper seeks to bring new insights to the pragmatics of translation – ways in which the literary translator grapples with meaning discernment and rendition when faced with texts couched in indigenized and hybridized linguistic forms, namely creoles, pidgins, camfranglais, and other forms of hybrid languages. There are clear and obvious benefits in literary indigenization (i.e., a larger audience, self-representation, etc) but how do these benefits transform when these languages are contextualized in literature? In what ways is pidginization complicit or at variance with imperial languages? And what are the ramifications of such complicity or variance for the translator? What forms of discursive agencies are made available through translation?